2015
DOI: 10.1111/pin.12323
|View full text |Cite
|
Sign up to set email alerts
|

L‐type amino acid transporter‐1 and CD98 expression in bone and soft tissue tumors

Abstract: L-type amino acid transporter-1 (LAT1) is expressed in many cancers. We examined LAT1 and CD98 expression immunohistochemically in surgically resected specimens of various bone and soft tissue tumors. Out of 226 cases, 79 (35%) were LAT1(+) and 95 (42%) were CD98(+) . In bone tumors, LAT1 was highly expressed in osteoblastoma (89%), chondrosarcoma (50%), and osteosarcoma (60%); in soft tissue tumors, LAT1 was highly expressed in rhabdomyosarcoma (80%), synovial sarcoma (63%), Ewing's sarcoma (60%), epithelioid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…The first barrier in cancer tissue involves the vascular blood wall, and extravasation from the bloodstream into the tumor tissue. After this EPR-driven leakage from blood vessels, the tumor environment (stromal tissue), i.e., acidic pH, facilitates liberation of free drugs that undergo rapid diffusion and reach tumor cells, after which transporter-driven rapid internalization occurs [1,3,30,31,54,57,59,72,73].…”
Section: Barriers To Delivery Of Drugs To Target Molecules In Tumor Cmentioning
confidence: 99%
“…The first barrier in cancer tissue involves the vascular blood wall, and extravasation from the bloodstream into the tumor tissue. After this EPR-driven leakage from blood vessels, the tumor environment (stromal tissue), i.e., acidic pH, facilitates liberation of free drugs that undergo rapid diffusion and reach tumor cells, after which transporter-driven rapid internalization occurs [1,3,30,31,54,57,59,72,73].…”
Section: Barriers To Delivery Of Drugs To Target Molecules In Tumor Cmentioning
confidence: 99%
“…In the canine lines, CD98 was not detected in the non-metastatic line but it was detected in the metastatic line indicating an increase. In OS, increased expression of CD98 has been observed in patient samples [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…There has been only one study investigating the expression of LAT1 and CD98 in sarcomas [13]. It reported that CD98 expression was higher than that of LAT1 in some bone tumors (67% vs. 47%, p<0.006); however, the percentage of CD98 expression was lower in soft tissue tumors than in bone tumors (28% vs. 67%).…”
Section: Discussionmentioning
confidence: 99%
“…The clinicopathological significance of LAT1 and CD98 expression in human epithelial tumors has been highlighted, but little is known about their expression in soft tissue tumors. Recently, Koshi et al immunohistochemically examined LAT1 and CD98 expression in 226 surgically-resected tumor tissues of bone and soft tissue origin [13], and reported that LAT1 and CD98 were positively expressed in 35% and 42% of these, respectively. They investigated the clinicopathological significance of these markers, using 4 samples of angiosarcoma; however, they did not draw any clear results regarding the expression of LAT1 and CD98.…”
mentioning
confidence: 99%